Iconic Meaning and Index Meaning of Traditional Culinary in Labuhanbatu: Ecolinguistic Study - Liani Hasnita Ulfa Br Sagala; Safrina Noorman (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
The Labuhanbatu is a regency of North Sumatera, its seat is Rantau Prapat. Not only famous for its oil palm and rubber plantations, but also famous for its variety of culinary delights and the uniqueness of its culinary naming. Usually culinary naming is based on iconic meaning and index meaning. This paper focuses on description iconic meaning and index meaning of traditional culinary in Labuhanbatu and also describes the relationship between aspects with iconic meaning and index meaning. In this research, the writer uses qualitative method with ecolinguistic review. The data of this research are Labuhanbatu culinary names. The method of data collection is done by in-depth interviews and literature study. The result of iconic meaning and index meaning of traditional culinary in Labuhanbatu’s culineries are: (1) anyang terubuk, whose name have the iconic meaning is reflected in the fish's cooking process, which is 'anyang' or chopped raw, and instead of using fire, it is cooked by smearing a concoction of seasonings on the fish (2) pajri nonas, whose name have the indexical meaning is found in the dish’s name, which is reflected in the ingredients used.  (3) anyang buas-buas, whose name have the iconic meaning of the name is shown in the way the dish is processed by ‘dianyang’ or by cutting the leaves raw and cooking it by smearing the dish with a variety of spices.  (4) pongat jelok, whose name have the indexical meaning of it exists because the dish holds the nature of bringing togetherness and has a particular philosophy to the community related to their customs. (5) sarak terong, whose name have the iconic meaning of it is shown in the main ingredient used. The ingredient is the eggplant which displays that the eggplant icon is the sign, and the relationship between the signifier and the sign is scientifically accompanying.